Technology supports me: Perceptions of the benefits of digital technology in adolescents - Bitto Urbanova, Laura; Madarasova Geckova, Andrea; Dankulincova Veselska, Zuzana; Capikova, Silvia; Holubcikova, Jana; van Dijk, Jitse P.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2023)
Background: Modern technology plays a significant role in adolescents’ life. Our knowledge is predominantly based on the research exploring its risks, but adolescents also feel this technology supports their life. Less attention has been paid to the latter. Therefore, our aim was to examine how adolescents perceive the benefits of modern technology. Methods: We used data from a qualitative study that was performed as part of international Health Behaviour in School-aged Children study. We conducted online semi-structured interviews with 15 Slovak adolescents that came from three different types of high school regarding its graduation system (mean age: 15.33; 20% boys). The data were analysed by using the consensual qualitative research and thematic analysis. Results: From adolescents´ statements we identified five main themes: 1. I know (source of information, formal and non – formal education); 2. I can (smart device, helpful tool); 3. I am connected/included (social interactions); 4. I have my comfortable place (leisure time, creating my alternative world); and 5. I work on my future (self-development). Conclusions: Adolescents perceived modern technology as a mostly supportive and helpful tool in their life. The opportunities of modern technology that they perceive should be better accommodated in public perception and policy as the societal debate is mostly dominated by perceived disadvantages and risks.